Emergence of lineage ST150 and linezolid resistance in Enterococcus faecalis: a molecular epidemiology study of UTIs in Tehran, Iran - Seyedolmohadesin, Maryam; Kouhzad, Mobina; Götz, Friedrich; Ashkani, Maedeh; Aminzadeh, Soheila; Bostanghadiri, Narjess (Frontiers in Microbiology, 2024)
Background: Urinary tract infections (UTIs) represent one of the most prevalent bacterial infections, with Enterococcus species now recognized as the second leading cause of these infections. This study focused on symptomatic UTI cases to investigate the risk factors associated with Enterococcus faecalis clinical isolates in patients from Tehran, Iran. Methods: Urine samples were collected from patients presenting with symptomatic UTIs. The identification of E. faecalis isolates was performed using standard microbiological techniques, with confirmation via polymerase chain reaction (PCR). Antibiotic susceptibility testing was conducted using the Kirby-Bauer disc diffusion method. The presence of virulence genes was determined through PCR, and biofilm formation was assessed using the microtiter plate method. Additionally, multi-locus sequence typing (MLST) was utilized to genotype linezolid-resistant isolates. Results: Out of 300 UTI cases, E. faecalis was identified as the causative agent in 160 instances. Notably, a high proportion of these isolates exhibited resistance to tetracycline (83.8%) and minocycline (82.5%). Linezolid resistance was observed in 1.3% (n=2) of the isolates. Conversely, the highest susceptibility rates were observed for vancomycin, penicillin G, ampicillin, and nitrofurantoin, each demonstrating a 98.8% susceptibility rate. Biofilm formation was detected in 25% of the E. faecalis isolates. A significant majority (93.8%) of the isolates harbored the efbA and ace genes, with varying frequencies of esp (72.5%), asa1 (61.2%), cylA (52.5%), and gelE (88.8%) genes.MLST analysis demonstrated that both linezolid-resistant isolates, characterized by strong biofilm formation and the presence of virulence genes, were assigned to the ST150 lineage, which has not been previously documented in clinical settings. Conclusions: The emergence of the ST150 clonal lineage, underscores its clinical significance, particularly in relation to linezolid resistance in E.faecalis. This study adds to the growing body of evidence linking specific clonal lineages with antibiotic resistance, highlighting the critical need for ongoing surveillance and molecular characterization of resistant pathogens.